(untitled) (Palíndromo, 2019)
Michael Schwab Editor of the Journal for Artistic Research (JAR) Translation Osmar Yang and Yara Guasque Article originally published in English (SCHWAB, Michael. "The Exposition of Practice as Research as Experimental Systems", 2014, pp. 31-40) as a chapter in the book CRISPIN, Darla; GILMORE, Bob (Eds.). Artistic Experimentation in Music. An Anthology. Leuven: Leuven University Press, 2014.